Development Of Reading Teaching Materials Indonesian For Class VII SMP With Dick And Carey Models - Muhammad Ramdan (UMSU, 2020)
. At the practical level, reading textbooks based on the Dick and Carey models get good results based on student descriptions when learning takes place. In the RPP implementation instrument, the results were 89%. This shows that reading teaching materials based on the Dick and Carey model are suitable for teaching reading in schools because they are very practical.